THE USAGE OF TECHNOLOGY APPLICATIONS FOR BILINGUAL EDUCATION OF CHILDREN - Matluba , Isoqjon qizi Turdieva (Innovative Development in Educational Activities, 2023)
Technology is now a crucial component of how students learn languages. This article’s goal is to review the literature on using technology to enhance bilingual education for kids. Without regard to the percentage of each language, the definition of bilingualism is participation in at least two (or more) languages, at least one of which is English. This study aims to ascertain how multilingual youngsters who speak both Indonesian and English use technology. The majority of studies have revealed that technology aids in children’s acquisition of bilingualism. Supporting bilingual youngsters necessitates tailoring abilities to their needs. The development of children’s language was strongly correlated with interactions between adults and youngsters. Additionally, in order to develop bilingual education without sacrificing mother tongue, interaction between parents and teachers was necessary.